Sex differences in anxiety and depression: insights from adult rodent models of chronic stress and neural plasticity - Bowman, Rachel; Frankfurt, Maya; Luine, Victoria (Frontiers in Behavioral Neuroscience, 2025)
The often co-morbid conditions of depression and anxiety are the most common mental illnesses and are more prevalent among females than males. Chronic stress paradigms in rodents serve as valuable preclinical models for investigating the factors contributing to these disorders and their neural underpinnings. A variety of chronic stressors are associated with the development of sexually differentiated effects on anxiety- and depressive-like responses in rodents. This review summarizes and discusses common behavioral tasks used to assess anxiety-like (e.g., elevated plus maze, open field) and depressive-like (e.g., sucrose preference, forced swim) behaviors in rodents and discusses evidence of sex differences in these responses. Preclinical chronic stress models also aid in identifying potential mechanisms underlying behavioral changes, including dendritic synaptic alterations in neural circuits affected by stress. Robust sex differences have been observed in stress-responsive brain regions such as the prefrontal cortex, hippocampus, and amygdala. Therefore, applying chronic stress paradigms and assessing their neural effects in rodents may provide crucial insights into the biological basis of sexually differentiated mental illnesses in humans.